Pengembangan UMKM Melalui Inovasi Produk Barokah 717 Di Desa Ambulu Kecamatan Sumberasih Kabupaten Probolinggo - Syahwa Ramadhan; Maharani Ikaningtyas (Pusat Riset dan Inovasi Nasional, 2023)
Ambulu Village is a village in Sumberasih District, Probolinggo Regency which has several MSME actors including potato donut sellers, pastry sellers, food sellers, caterers, and others. This research focuses on the development of product innovation at Barokah 717 SMEs in Ambulu Village. UMKM Barokah 717 is one of the UMKM that produces banana and cassava chips in Ambulu Village, Sumberasih District, Probolinggo Regency which is liked by the local community and becomes souvenirs for tourists who are in Probolinggo. Based on the results of interviews with MSME actors, it was found that their products were sold conventionally so that consumers were only in Ambulu Village and its surroundings. Therefore, it is necessary to design product development starting from packaging, branding, to product innovation so that it can expand market share. The results of this research are also expected to improve the community's economy and advance other MSMEs so that they can innovate in producing a higher quality product and are able to penetrate a wider market.